Looking beyond enrollment rates: The long-term influence of preschool science curricula on children’s science achievement - Saçkes, Mesut; Cabe Trundle, Kathy (Journal of childhood, education & society (Online), 2024)
This study provides evidence that what happens in preschool (i.e., preschool curriculum) can have long-term consequences years later. In the current study, we seek to answer the question of whether the inclusion of science in the preschool curriculum is associated with fourth- and eighth grade science achievement scores. Based on science achievement data from the Trends in International Mathematics and Science Study (TIMSS 2015 and 2019 cycles), the quality of preschool science learning opportunities showed long-term impacts on science achievement at the fourth grade level. Even after controlling for enrollment rates, the quality of the preschool curricula was a statistically significant predictor of fourth grade science scores with a high effect size (d=0.74). The observed impacts, however, appeared to diminish by eighth grade. Results from this study suggest that science concepts and skills should be an integral part of preschool curricula and curricular frameworks, and policy makers should allocate resources to provide well-designed preschool education programs with high quality curricula.